Pengaruh Budaya Organisasi, Motivasi dan Lingkungan Kerja Terhadap Kinerja Pegawai PERUMDA Air Minum Bayuangga Kota Probolinggo - Muhammad Anwar Jazuli; Mutinda Teguh Widayanto; Agustina Pujiastuti (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
Employee performance can be carried out to the maximum if conditions are properly satisfied. One of the factors in order to improve performance is organizational culture, motivation and an adequate work environment. This experiment is to determine the impact of organizational culture, motivation and work environment through simultaneous, partial and knowing the dominant variable on performance. This experimental method is quantitative through a causal associative approach. The experimental population is all employees, totaling 80 employees. The sampling technique uses saturated sampling. A sample of 80 respondents. Data were collected through questionnaires and completed through data analysis techniques through validity testing, reliability testing, classical assumption testing, multiple regression analysis, coefficient of determination (R-Square) and hypothesis testing. The experimental results show that the physical work environment and work motivation partially and simultaneously have a significant impact on employee performance. The dominant impact in this experiment is work motivation.